Electrical Transport properties of Ni-Cr binary alloys - Suthar, P. H.; Thakore, B. Y.; Gajjar, P. N. (Communications in Physics, 2014)
Electrical transport properties viz. electrical resistivity and thermal conductivity of Ni-Cr binary alloys are determine by our recognized single parametric model potential in wide range of Cr concentration. In this work, screening functions (Ichimaru and Utsumi, Farid et al. and Sarkar et al.) are employed along with the Hartree and Taylor functions to study the relative influence of the exchange and correlation effect. Given liquid alloys are studied as a function of their composition at three different temperatures according to Faber-Ziman model. Computed values of electrical transport properties are in good agreement with the experimental data available in literature.